EPIDEMIOLOGI DAN RESISTENSI ANTIBIOTIK SALMONELLA TYPHI DAN PARATYPHI A PADA KASUS DEMAM TIFOID DI JAKARTA: A SYSTEMATIC LITERATURE REVIEW - Giovanny Hasiholan Simatupang, Erald; Diah Pramesti Ken Wardana, Kadek; Ivanka, Dhea (Lafadz Jaya Publisher, 2023)
Typhoid fever remains a significant public health concern in Jakarta. Antibiotic resistance in Salmonella Typhi and Paratyphi A bacteria poses a challenge in typhoid management. To provide a comprehensive overview of antibiotic resistance patterns in S. Typhi and P. A in Jakarta, a systematic literature review was conducted. This study utilized data from Scopus, ScienceDirect, and ResearchGate databases. The findings reveal that several studies reported resistance to fluoroquinolone antibiotics, such as ciprofloxacin, which is the first-line treatment for typhoid fever. Additionally, some studies noted a high level of resistance to beta-lactam antibiotics, such as ampicillin and ceftriaxone, commonly used to treat S. Typhi and P. A infections. The implications of these findings call for active involvement from the government, healthcare professionals, and the community in addressing antibiotic resistance in typhoid fever. Collaborative efforts are needed to enhance surveillance and monitoring of antibiotic consumption, as well as to implement proper education for the public on rational antibiotic use. The development of new antibiotics and further research on antibiotic resistance are also crucial to exploring effective treatment alternatives.